Therapy With Carboplatin and Anti-PD-1 Antibodies Before Surgery Demonstrates Sustainable Anti-Tumor Effects for Secondary Cancers in Mice With Triple-Negative Breast Cancer - Gao, Meizhuo; Wang, Tie; Ji, Litong; Bai, Shuping; Tian, Lining; Song, Hongjiang (Frontiers in Immunology, 2020)
Patients with triple-negative breast cancer (TNBC) suffer an unfavourable prognosis. Carboplatin (CBDCA) as a cytotoxic reagent has been widely administered to patients with cancer including TNBC. Programmed cell death protein 1(PD-1) is an immune checkpoint, blockade of which unleashes T cell functions that kill cancer cells. However, the efficacy of CBDCA combined with anti-PD-1 antibodies in TNBC has not been determined. Patient-derived xenografts (PDX) were implanted to immune-deficient mice. Three mouse TNBC cell lines (4T1, EMT6, and E0771) were seeded to immune-competent mice. Tumor volumes and survival rates were monitored. CBDCA and anti-PD-1 antibodies were administered by intra-peritoneal injection at designated time points. Total CD8+ T cells, memory CD8+ T cells, and CD103+ dendritic cells (DC) in the tumor were measured by flow cytometry. Tumor-specific CD8+ T cells were quantified by the ELISpot assay. Administration of CBDCA to PDX-bearing mice induced increased levels of tumor cell necrosis and reduced tumor size. Treatment with CBDCA and anti-PD-1 antibodies reduced TNBC tumor volumes and slightly improved survival rates. More importantly, therapy with CBDCA and anti-PD-1 antibodies before surgery showed a remarkably improved, sustainable protection against a secondary tumor after surgery by a CD8+- T-cell-dependent manner, which required CCL4 expressed in the tumor and subsequently CD103+ DC recruited to the tumor microenvironment. Immunochemotherapy with CBDCA and anti-PD-1 antibodies before surgery improves the outcome of a secondary tumor after surgery via increasing the number of tumor-specific CD8+ T cells in the tumor microenvironment of murine TNBC. These results highlight the possibility to utilize this regimen in clinical practice.